A review of protein adsorption and bioactivity characteristics of poly ε-caprolactone scaffolds in regenerative medicine. (5th January 2022) - Abdal-hay, Abdalla; Sheikh, Faheem A.; Gómez-Cerezo, N.; Alneairi, Abdulrahman; Luqman, Monis; Pant, Hem Raj; Ivanovski, Saso
Graphical abstract: Abstract: The failure of transplanted tissues and organs is a major challenge in contemporary regenerative medicine. Biocompatible scaffolds, fabricated from poly ε-caprolactone (PCL), are widely used in tissue engineering strategies to promote tissue and organ growth; however, scaffold biological activity and safety refinement are urgently needed to support their use in clinical practice. PCL scaffolds created in 2-D or 3-D forms have emerged with great potential for the development of tissue regeneration grafts. However, limited bioactivity and surface wettability render PCL scaffolds direct interactions with surrounding tissues. Manipulations of PCL scaffolds may have the potential to overcome these limitations. This review focuses on how scaffold manipulations enhance protein adsorption and can achieve optimized scaffold biocompatibility. From a practical perspective, techniques such as etching or deposition of bioactive compounds can easily modify the surface of the PCL scaffolds. Incorporating bioactive inorganic fillers can be an alternative way to enhance the bioactivity of PCL scaffolds. This review summarizes recent advances in the development of bioactive PCL scaffolds and their applications in regenerative medicine.